2023
DOI: 10.1007/s40121-023-00803-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genomic Evolution of Carbapenem-Resistant Klebsiella pneumoniae Bloodstream Infections over Two Time Periods at a Tertiary Care Hospital in South India: A Prospective Cohort Study

Abstract: Introduction:The objective of this study was to examine the evolution of carbapenem-resistant Klebsiella pneumoniae (CRKp) infections and their impact at a tertiary care hospital in South India.Methods: A comparative analysis of clinical data from two prospective cohorts of patients with CRKp bacteremia (C1, 2014-2015; C2, 2021-2022) was carried out. Antimicrobial susceptibilities and whole genome sequencing (WGS) data of selected isolates were also analyzed. Results: A total of 181 patients were enrolled in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Our results are different from a recently published study from South India that has shown no difference in mortality after introducing ceftazidime–avibactam ± aztreonam for the treatment of CRKP infections. However, it must be noted here that the study was conducted in two different timelines where improvement in supportive care could influence the results despite the adjustments [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are different from a recently published study from South India that has shown no difference in mortality after introducing ceftazidime–avibactam ± aztreonam for the treatment of CRKP infections. However, it must be noted here that the study was conducted in two different timelines where improvement in supportive care could influence the results despite the adjustments [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are different from a recently published study from South India that has shown no difference in mortality after introducing ceftazidime-avibactam ± aztreonam for the treatment of CRKP infections. However, it must be noted here that the study was conducted in two different timelines where improvement in supportive care could in uence the results despite the adjustments [19].…”
Section: Resultsmentioning
confidence: 99%
“…5,10–13 In particular, K. pneumoniae has developed rapid resistance to carbapenems, which are highly effective beta-lactam based antibiotics which inhibit bacterial cell wall synthesis. 9,14 The development of extended spectrum beta-lactamase genes (EBSL) has also given rise to a secondary genetic and phenotypic resistance to quinolones. 5,6,14,15 Quinolone-based antibiotics target either DNA helicase or DNA topoisomerase II/IV, both of which contain peptide subunits gryA and parC.…”
mentioning
confidence: 99%